2021
DOI: 10.1111/pai.13545
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal ritodrine hydrochloride administration during pregnancy and childhood wheezing up to three years of age: The Japan environment and children's study

Abstract: Background:The effects of maternal ritodrine hydrochloride administration (MRA) during pregnancy on fetuses and offspring are not entirely clear. The present study aimed to evaluate the association between MRA and childhood wheezing using data from a nationwide Japanese birth cohort study.Methods: This study analyzed the data of the participants enrolled in the Japan Environment and Children's Study, a nationwide prospective birth cohort study, between 2011 and 2014. Data of women with singleton live births af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Parity was categorized as nulliparous or multiparous. Participants provided information about their smoking status by selecting one of the following: "Currently smoking," "Never," "Previously did but quit before realizing current pregnancy," and "Previously did but quit after realizing current pregnancy;" the smoking category included those who chose "Currently smoking," whereas the non-smoking category consisted of the remainder [23]. Maternal educational status was categorized into the following four groups according to the number of education years: (1) junior high school, < 10 years;…”
Section: Primary Outcome and Confounding Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parity was categorized as nulliparous or multiparous. Participants provided information about their smoking status by selecting one of the following: "Currently smoking," "Never," "Previously did but quit before realizing current pregnancy," and "Previously did but quit after realizing current pregnancy;" the smoking category included those who chose "Currently smoking," whereas the non-smoking category consisted of the remainder [23]. Maternal educational status was categorized into the following four groups according to the number of education years: (1) junior high school, < 10 years;…”
Section: Primary Outcome and Confounding Factorsmentioning
confidence: 99%
“…(2) high school, 10-12 years; (3) technical/vocational college or university, 13-16 years; and (4) graduate school, ≥ 17 years [23]. Annual household income was categorized into the following four groups: (1) < 2,000,000 JPY; (2) 2,000,000-5,999,999 JPY; (3) 6,000,000-9,999,999 JPY; and (4) ≥ 10,000,000 JPY [23]. Mode of delivery was divided into vaginal delivery and cesarean section [24].…”
Section: Primary Outcome and Confounding Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the evaluation of the effects of tocolytic agents on fetal and neonatal conditions may elucidate the utility of tocolysis. 14,15…”
Section: Problems Of Ptb Prevention In Japanmentioning
confidence: 99%
“…Although previous studies have shown that MRA causes fetal tachycardia [ 23 – 25 ], its clinical significance is still unclear. Similarly, although recent studies have reported that MRA is associated with increased incidence of childhood asthma and wheezing in offspring [ 26 , 27 ], it is unclear whether short-term MRA exhibits the same relationship. Furthermore, the effects of MRA on fetuses exposed to intraamniotic inflammation have not been reported.…”
Section: Introductionmentioning
confidence: 99%